Prediction of Heart Disease with Claims Data using Machine Learning Method - Lavanya, L; Megha, V; Nagashree, H; Pavithra, S; K L, Anusha (International Journal of Computer Sciences and Engineering, 2025)
Machine learning can be referred as discovery of relationships in larger datasets and in some cases it is used for predicting relationships based on the results discovered. Nowadays machine learning is achieving widespread in various fields such as healthcare industry, scientific and engineering. In healthcare industry, machine learning is mainly used for disease prediction. The main objective of our work is to predict heart disease using Naïve Bayes classifier. Naïve Bayes are the probabilistic classifiers used to classify the data using attributes. It retrieves the trained data and compares the attribute values with test data sets and predicts the result.